EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN NUMERASI SISWA KELAS IV DI SD NEGERI 61 PRABUMULIH - Oktariani, Siwi; Arafat, Yasir; Selegi, Susanti Faipri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model on the numeracy skills of fourth-grade students at SD Negeri 61 Prabumulih. The research approach used is quantitative with a pre-experimental method. The research design used is a One-Group Pretest-Posttest design. The population of this study consisted of 18 fourth-grade students at SD Negeri 61 Prabumulih. The sample used is a saturated sample, where all members of the population are used as the sample. Data collection techniques involved pretests and posttests. The data analysis techniques used for processing the data include normality tests to check the prerequisites and an Independent t-test to test the hypothesis. The results of the t-test showed t_calculated = 2.522 > t_table = 0.032. Therefore, H? is rejected and H? is accepted, indicating that the Problem-Based Learning (PBL) model is effective in improving the numeracy skills of fourth-grade students at SD Negeri 61 Prabumulih.